VIDEO 360 PENGENALAN OBJEK WISATA BENTENG OTANAHA DI PROVINSI GORONTALO DENGAN METODE MDLC - Rahmad, Wahyu Annur; Koniyo, Moh. Hidayat; Zakaria, Alfian (Gorontalo State University, 2024)
This research is motivated by the difficulties faced by visitors in exploring the tourism site. During their visit, visitors often need to ask the ticket attendant for information about the best spots to visit due to the lack of informative signs. The aim of this research is to develop a virtual tour product using video technology 360 for Otanaha Fortress by employing the Multimedia Development Life Cycle (MDLC) method, which includes the stages of concept, design, material collection, production, testing, and distribution stages. This research is expected to contribute to the development of innovative and interactive tourism information media and promote Otanaha Fortress as one of the tourist destinations in Gorontalo Province. Keywords: Multimedia Development Life Cycle (MDLC); Otanaha Fortress of Gorontalo; virtual tour; 360 video.